Secrecy Sum Rate Optimization in MIMO NOMA OSTBC Systems with Imperfect Eavesdropper CSI - Yan, Jianfei; Deng, Zhishan; Chen, Qinbo (Communications and Networking, 2019)
In this research, we investigate the secrecy sum rate optimization problem for a multiple-input multiple-output (MIMO) non-orthogonal multiple access (NOMA) system with orthogonal space-time block codes (OSTBC). We construct a model where the transmitter and the relay send information by employing OSTBC, while both the source and the relay have imperfect channel state information (CSI) of the eavesdropper. The precoders and the power allocation scheme are jointly designed to maximize the achievable secrecy sum rate subject to the power constraints and the minimum transmission rate requirements of the weak user. To solve this non-convex problem, we propose the constrained concave convex procedure (CCCP)-based iterative algorithm and the alternative optimization (AO) method, where the closed-form expression for power allocation is derived. The simulation results demonstrate the superiority of our proposed scheme.